Amyotrophic lateral sclerosis in a patient with chronic lymphocytic leukaemia and drug related sarcoid-like reaction - Joumana Freiha; Effie Grand; Ben Marshall; Ramamurthy Arunchalam; Ashwin Pinto; Chinar Osman (BMC Neurology)
Abstract Sarcoid-like reaction is an immunological reaction that can affect lymph nodes and organs but does not meet the diagnostic criteria for systemic sarcoidosis. Anti-CD20 auto-antibodies have been reported to be responsible for such reactions. There are several reported associations between Chronic lymphocytic leukaemia (CLL), Amyotrophic lateral sclerosis (ALS) and Sarcoid-like reactions (SLR). We report a case of ALS developing in a patient with treated CLL and drug related SLR one day after exposure to Venetoclax and Rituximab. A 60-year-old male presented with lower limb rash, left leg weakness followed by bulbar symptoms which progressed over 12-months. Workup demonstrated a Cerebrospinal fluid (CSF) pleocytosis and inguinal lymphadenopathy. Skin and inguinal lymph node biopsies showed non-necrotising granulomata. Electromyography met diagnostic criteria for ALS. He was treated for presumed neurosarcoidosis mimicking ALS. Despite prednisolone and infliximab treatment, the motor symptoms rapidly progressed; Hence, we made a clinical diagnosis of ALS. We discuss the diagnostic and treatment challenges of this case.